A butch among the belles - Strickland, Bonnie R. (Journal of Lesbian Studies, 2002)
This memoir of a 65-year-old “butch” lesbian describes her growing-up days in the South and her subsequent professional identity as a university professor and psychologist. The article includes feelings about being raised as a girl while feeling male. Personal reactions to family pressures to conform to a rigid sex role are noted and some attention is given to the effects of living an adult life in the closet.
Keywords: amériques; butch; identités LGBTQIA2+; personnes lesbiennes; ressource en ligne; régions géographiques; sexualité; thématiques; états-unis